Se busca una raíz unitaria: evidencia para Chile - Chumacero, Rómulo (Estudios de Economía, 2016)
This paper presents compelling evidence against the null hypothesis of a unit root in series such IMACEC, consumption or GDP for the Chilean economy. This evidence builds on results derived by Chumacero (2000) that show that when the scale variable is difference stationary, the returns on assets should present a behavior that is not supported by the data. Thus, care should be taken when using econometric models that impose unit roots based on traditional tests.